2021
DOI: 10.1021/acs.est.1c05521
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Organic Nitrates to Organic Aerosol over South Korea during KORUS-AQ

Abstract: The role of anthropogenic NOx emissions in secondary organic aerosol (SOA) production is not fully understood but is important for understanding the contribution of emissions to air quality. Here, we examine the role of organic nitrates (RONO2) in SOA formation over the Korean Peninsula during the Korea–United States Air Quality field study in Spring 2016 as a model for RONO2 aerosol in cities worldwide. We use aircraft-based measurements of the particle phase and total (gas + particle) RONO2 to explore RONO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 106 publications
4
8
0
Order By: Relevance
“…The nitrogen atoms in OOMs are assumed to be mainly associated with the nitrate group (−ONO 2 ) formed from bimolecular reaction between RO 2 radical and NO. Field measurements have also shown that up to 77 % of molecules in organic aerosol (OA) contain nitrate functional groups under different atmospheric conditions (Ditto et al, 2020;Kenagy et al, 2021;Kiendler-Scharr et al, 2016;Lee et al, 2016;Ng et al, 2017;Lin et al, 2021;Rollins et al, 2013;Xu et al, 2015;Ye et al, 2021;Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The nitrogen atoms in OOMs are assumed to be mainly associated with the nitrate group (−ONO 2 ) formed from bimolecular reaction between RO 2 radical and NO. Field measurements have also shown that up to 77 % of molecules in organic aerosol (OA) contain nitrate functional groups under different atmospheric conditions (Ditto et al, 2020;Kenagy et al, 2021;Kiendler-Scharr et al, 2016;Lee et al, 2016;Ng et al, 2017;Lin et al, 2021;Rollins et al, 2013;Xu et al, 2015;Ye et al, 2021;Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The mass concentration of total particulate organic nitrate (pON) can be estimated by assuming a molecular weight for the pON (MW pON ; eq ). Previous studies ,,,,, have assumed the MW of pON between 200 and 300 g mol –1 . However, we used MW pON = 265 g mol –1 (with 200 and 330 g mol –1 as lower and upper limits of MW pON , respectively) based on earlier FIGAERO-CIMS measurements conducted at SMEAR II during the spring of 2014 …”
Section: Methodsmentioning
confidence: 99%
“…gON can also form via the minor pathway when organic peroxy radicals (RO 2 ), for example, from VOC oxidation, react with NO . Several field measurements throughout the world, both in regions dominated by BVOCs and anthropogenic VOCs (AVOCs), have recognized pON as a substantial part of the submicron organic aerosol. Previous laboratory studies of different VOC + NO 3 radical systems have regularly reported high SOA mass yields (several tens of percent, Table 2 in Ng et al), emphasizing the importance of these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that vehicular IVOCs contribute significantly to SOA, implying the importance of reducing IVOCs when making air pollution control policies in urban areas of China and the EU as well. The role of I/SVOCs has been highlighted in other studies, and the missing source may result from the oxidation of semi- and intermediate-volatility organic compounds and/or from anthropogenic molecules that undergo autoxidation or multiple generations of OH-initiated oxidation involving organic nitrates [ 172 ].…”
Section: Scientific Backgroundmentioning
confidence: 99%